ECONOMIC VALUATION STUDY OF GEMBIRA LOKA YOGYAKARTA ZOO - Fallo, Trisno; Nugroho, Andri Prasetyo; Setyowati, P. Ratna; Edi Laksono, Gangsar; Doni, Doni; Farras, Farras (Universitas Negeri Medan, 2024)
The aim of this study is to analyze the potential total economic value of the Gembira Loka Zoo tourist area and also as input and consideration in making policies regarding the management of the Gembira Local Zoo tourist area, both for the management and the government. Primary data collection techniques were carried out through survey and interview methods in the form of onsite using questionnaires. This research uses a direct approach with market value, surrogate market costs through the travel cost method and contingent valuation method (CYM) as well as to assess the benefits produced (products and services) by the Gembira Loka Zoo. Based on the results of the analysis, a study of the total economic value of the Gembira Loka Zoo zoo area, it can be concluded that the direct use value of the Gembira Loka Zoo zoo in 2023 is IDR. 333,585,267,958.80, and was obtained from calculating travel costs incurred by respondents with total ticket income. The indirect use value of the Gembira Loka Zoo zoo in 2023 was IDR 1,419,904,680.12, and was obtained from an economic assessment of the ecological benefits of forest areas in zoos, namely as a carbon absorber and water catchment, while the economic value of preservation aims to calculate respondents' willingness to participate in preserving animals at Gembira Loka Zoo. The total preservation value is IDR 39,264,801,732 and the total economic valuation of Gembira Loka Zoo is IDR. 374,269,974,370.92.